Clinical and molecular analyses of bloodstream infections caused by IMP metallo-β-lactamase-producing Enterobacteriaceae in a tertiary hospital in Japan. Issue 1 (January 2020) - Mori, Nobuaki; Kagawa, Narito; Aoki, Kotaro; Ishi, Yoshikazu; Tateda, Kazuhiro; Aoki, Yasuko
Abstract: Carbapenemase-producing Enterobacteriaceae infection has been reported worldwide and is a major threat to public health. However, reports of bloodstream infection (BSI) caused by metallo-β-lactamase (MBL), especially the IMP-type, are limited. Therefore, we aimed to investigate the clinical and microbial characteristics of patients with BSI caused by IMP-type MBL-producing Enterobacteriaceae (MBL-E) in a tertiary care hospital in Japan. The clinical data were collected from medical charts for all the patients. A next-generation sequencing approach and multilocus sequence typing were used to identify antimicrobial resistance genes. Six patients were enrolled and had severe conditions on admission. The sources of MBL-E BSI were as follows: catheter-related BSI, pyelonephritis, cholangitis, and bacterial peritonitis. No isolate was resistant to levofloxacin or aminoglycoside. Microbiological response rates were 100%. The all-cause 30-day mortality rate was 50%. Of the six isolates, three were Enterobacter hormaechei sequence type 78, one was Enterobacter cloacae Hoffman cluster IV ST997, and two were Klebsiella pneumoniae (ST134 and ST252). All isolates produced IMP-1 and carried bla IMP-1 gene and various antimicrobial resistance genes. The results of this study showed that MBL-E BSI was fatal, although rare, in patients with severe diseases and long-term hospitalization. Further research is necessary to determine the appropriate treatment strategies for MBL-producing BSI.